Answer: Ln( (1/9)*a^3*b^2) = 3*Ln(a) + 2*Ln(b) - Ln(9)
Explanation:
Here we need to use the relations:
Ln(x^y) = y*Ln(x)
Ln(x*y) = Ln(x) + Ln(y)
Ln(x/y) = Ln(x) - Ln(y)
Then, we have:
Ln( (1/9)*a^3*b^2)
First we could use the second relation to rewrite this as:
Ln(1/9) + Ln(a^3) + Ln(b^2)
Now we can use the third relationship to rewrite the first term as:
ln(1/9) = ln(1) - ln(9) = -ln(9)
Then our equation becomes:
Ln(1/9) + Ln(a^3) + Ln(b^2) = Ln(a^3) + Ln(b^2) - ln(9)
Now we can use the first relation to rewrite this as:
Ln(a^3) + Ln(b^2) - ln(9) = 3*Ln(a) + 2*Ln(b) - Ln(9)
And that is all the simplifications we can do.